Грегор фон Реццорі: зразок передчуття постмодерністського стилю - Басняк, Т. (Питання літературознавства, 2009)
Авторську іронію Реццорі досліджено в аспекті її креативного потенціалу. Доведено, що суміщення часових координат приватної творчої діяльності письменника з суспільно історичними параметрами стилю відповідної доби виразно не співпадає, це сприяє утворенню парадоксального іронічного топосу, зовсім не притаманного практиці модерністського письма. Прозову спадщину надзвичайно самобутнього автора вперше розглянуто в ключових вимірах постмодерністської естетики. Under existing conditions of multiculturalism which declares “cultural diversity – racial, ethnical, regional, gender, sexual – that is a wide range of diversity” imagological investigation of fiction is especially actual. Imagology which studies national images of the world and represents an important aspect of literary comparative studies gives a possibility to characterize formation and productivity of images of Another in national literatures, to comprehend the nature of dialogue between nations and cultures. The paper deals with functions of Another in the contemporary English novel (D. Lodge, A. Hollinghurst) taking into consideration the influence of national stereotypes on image-making.